Explaining the electoral performance of populist parties: the Netherlands as a case study - Stijn van Kessel (2011)
This article provides an explanatory framework for the electoral performance of populist parties, using the Netherlands as a case study. The Netherlands is an ideal case, as several populist parties have entered the political scene in recent years with varying levels of electoral success. The most notable cases are the List Pim Fortuyn and Geert Wilders' Freedom Party. Whereas the former party did not sustain, Geert Wilders has, so far, managed to remain an important force in Dutch politics. The article argues that the performance of populist parties is dependent on a combination of causal conditions: the availability of the electorate, the responsiveness of established parties and the supply of credible populist challengers. As will be argued, especially this latter factor is vital to the (long-term) performance of populist parties. Further research should, therefore, not refrain from taking the agency of populist parties themselves into account.